GIS for Landslide Risk Assessment, Study Case Pengasih and Sentolo District, Kulon Progo, Indonesia - Arrisaldi, Thema; Pratiknyo, Puji; Wilopo, Wahyu (TDMRC, Universitas Syiah Kuala, 2023)
Landslide is a natural phenomenon that often occurs as a disaster in Kulon Progo Region. This research is located in Pengasih and Sentolo District, Kulon Progo. The aim of the study is landslide risk mapping in the research area. The landslide risk map has 3 parameters, such as potential landslide condition, vulnerable situations, and community capacity to cope with the landslide disaster. Potential landslide obtained from Geographic Information System (GIS )overlay analysis using Analytical Hierarchy Process (AHP) consists of 4 sub-parameters: slope gradient (55.49%), geological condition (25.16%), stream density (9.67%), land use (9.67%). The vulnerability was obtained from 3 sub-parameters, such as economic vulnerability (33.33%), infrastructure vulnerability (33.34%), and population density (33.33%). The community capacity in the research area was obtained from The activity of the Region Disaster Management Authority (BPBD) of Kulon Progo to strengthen community awareness to cope with landslide disasters, such as socialization about landslides and simulation during an emergency landslide. The input in overlay analysis used GIS for the parameters are all sub-parameters from each parameter. Landslide risk map obtained from overlay analysis using GIS based on landslide potential map, vulnerability map, and capacity map. The result is that Pengasih and Sentolo Districts have low to moderate landslide risk conditions. Several landslides occur in each landslide risk zone.